2019
DOI: 10.1002/jmri.27027
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Automated Perfusion‐Weighted Phase‐Resolved Functional Lung (PREFUL)‐MRI in Patients With Pulmonary Diseases

Abstract: BackgroundPerfusion‐weighted (Qw) noncontrast‐enhanced proton lung MRI is a promising technique for assessment of pulmonary perfusion, but still requires validation.PurposeTo improve perfusion‐weighted phase‐resolved functional lung (PREFUL)‐MRI, to validate PREFUL with perfusion single photon emission computed tomography (SPECT) as a gold standard, and to compare PREFUL with dynamic contrast‐enhanced (DCE)‐MRI as a reference.Study TypeRetrospective.PopulationTwenty patients with chronic obstructive pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 32 publications
6
84
0
2
Order By: Relevance
“…Various image registration algorithms for pulmonary FD-MRI have been described in the existing literature (2,3,9,11,12,14,19,28). In the current study, the performance of three different image-registration algorithms for FD-MRI was analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various image registration algorithms for pulmonary FD-MRI have been described in the existing literature (2,3,9,11,12,14,19,28). In the current study, the performance of three different image-registration algorithms for FD-MRI was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, symmetric-diffeomorphic registration was performed by ANTs with following settings: image dimensions = 2; update field variance in voxel space (weight) = 1; metric radius = 9; number of iterations per level = 50 × 25 × 25; smoothing = Gaussian ][|3,1. Several studies dealing with pulmonary FD-MRI have utilized ANTs for image registration (1116).…”
Section: Methodsmentioning
confidence: 99%
“…Repeatability and validation studies of 2D PREFUL to reference standards have been performed to facilitate the use of 2D PREFUL in clinical routine. [20][21][22][23] Recently, 3D PREFUL has been developed to assess dynamic ventilation of the whole lung in an 8-minute acquisition, and the preliminary feasibility results in 16 study participants including patients with asthma, CF, and COPD have been presented. 24 However, the repeatability of ventilation parameters derived from 3D PREFUL, which is necessary to know prior to its use in clinical settings, has not been assessed.…”
mentioning
confidence: 99%
“…Ventilation 75 was validated in 12 patients with COPD and 14 patients with bronchiectasis with He‐3 MRI, CT, and PFT, 76 in 16 patients with asthma with He‐3 and PFT, 77 in 27 COPD patients with F‐19, 78 and in 20 CF patients and 20 healthy volunteers with PFT 79 . Free‐breathing MRI ventilation markers were found to correlate with PFT and ventilation defects agree with hyperpolarized MRI and F‐19.…”
Section: Ventilation and Perfusion Imagingmentioning
confidence: 83%
“…A quantification method, borrowed from arterial spin labeling (ASL) imaging, was introduced, but further validation is pending 74 . A recent study demonstrated a good correlation to single photon emission computed tomography (SPECT) in addition to DCE in CTEPH patients 75 . [Correction added on March 18, 2020, after first online publication: The missing reference number was added in the preceding sentence.…”
Section: Ventilation and Perfusion Imagingmentioning
confidence: 99%